2012
DOI: 10.1902/jop.2011.110076
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic Considerations for the Regional Anatomy in the Posterior Mandible

Abstract: Given the high degree of variability in mandibular bone volume surrounding the IAN and the position of the IAN, the use of CT scans should be considered for surgical procedures in the posterior mandible when there is risk of injury to the IAN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 22 publications
1
7
1
Order By: Relevance
“…The mean thickness of our measurements was similar to that obtained in other studies, such as the one performed by Levine [20][21][22] The results related to the thickness of the IDC demonstrated that, in all locations, the radiologically measured thickness was greater than the anatomically measured one (mean value of 0.3 mm).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The mean thickness of our measurements was similar to that obtained in other studies, such as the one performed by Levine [20][21][22] The results related to the thickness of the IDC demonstrated that, in all locations, the radiologically measured thickness was greater than the anatomically measured one (mean value of 0.3 mm).…”
Section: Discussionsupporting
confidence: 89%
“…[20][21][22] In our study, we did not find differences in relation to the thickness of the vestibular table based on gender or location. [20][21][22] In our study, we did not find differences in relation to the thickness of the vestibular table based on gender or location.…”
Section: Discussioncontrasting
confidence: 65%
“…Our data showed that BH dimensions were higher in males than in females, while BH dimensions decreased from premolar to molars. Similarly, a significant difference in bone height between males and females has been reported in the dentulous 1,2 , the edentulous 7 , and both types of individual (Table 8) [3][4][5]8,9 . On the other hand, Alrahaimi et al found no significant difference between males and females regarding distances from the alveolar crest to the superior position of the mandibular canal in a study on jaws with single missing teeth 6 .…”
Section: Discussionmentioning
confidence: 66%
“…These reports suggest that BMCs are more common than anticipated, their presence being confirmed using volumetric imaging (Claeys & Wackens, 2005). Nevertheless, one study that mapped the course of 390 mandibular canals using CT found no indications of a BMC (Yashar, Engeland, Rosenfeld, Walsh, & Califano, 2012 Among the first attempts at classification were those by Nortje, Farman, and de V Joubert 1977, Nortje, Farman, and Grotepass (1977),…”
Section: Dry Mandible/mri (%)mentioning
confidence: 99%